The Political Economy of Buzzer Actor Networks in Text Production - Al Amin, Ainur Rofiq; Fahmi, Muh. Yusrol (UIN Sunan Ampel Surabaya, 2024)
This article examines the network built by buzzers in the 2024 Presidential election. The basic assumption is that the buzzer phenomenon is an industry that affects political dynamics. This qualitative research uses network theory to identify the text production process carried out by buzzers, and uses a political economy approach to analyze the relationships formed between buzzers, agencies (buzzer industry) and politicians. Data were collected through interviews and documentation. The findings; first, there are 4 stages in the production of text on social media. This starts from the agency's process of recruiting potential buzzers to create texts according to the agency's framing. Second, the main actors of the buzzer industry are buzzers, agencies and politicians. In this relationship, the dominance of power is owned by the agency as an extension of politicians. The agency controls and encourages a narrative to be created. The first domination is done by politicians to the agency to produce text narratives according to their political interests. Then the agency transforms the interests of politicians or political parties to buzzers. Agencies and politicians are in the same line of interest, namely building a narrative of an interest. The visible relationship between the agency and the buzzer is a relationship between workers and service providers.